Effectiveness of Consuming Thalassa Eggplant and Date Extract in Increasing Hemoglobin Levels in Pregnant Women: Systematic Literature Review - Fitrianingsih, Ulfia; Runjati, Runjati; Simanjuntak, Betty Yosephin (GLOBAL HEALTH SCIENCE GROUP, 2025)
Anemia in pregnant women is a significant public health problem, especially in developing countries. Iron deficiency in pregnant women can interfere with fetal growth and maternal health. One alternative to increase hemoglobin levels is to consume local foods such as tamarillo and date palm juice, which are rich in iron and vitamin C.Objective: The aim of this study was to identify the effectiveness of consuming tamarillo and date palm juice in increasing hemoglobin levels in pregnant women with anemia based on a systematic literature review.Method: The research design is a Systematic Literature Review of articles or journals published in 2020-2024, accessed on Google Scholar, PubMed and Scopus with the Prisma Flow technique. Relevant articles were selected using the PRISMA flow technique, with the inclusion criteria being in Indonesian or English that can be accessed in full.Results: The results of the analysis of 10 articles showed that consumption of tamarillo and date palm juice significantly increased hemoglobin levels in pregnant women with anemia. The increase in hemoglobin levels ranged from 1.0-2.0 g/dL in the intervention group. Tamarillo is effective due to its vitamin C content which increases the absorption of non-heme iron, while date palm juice provides additional iron and energy to support hemoglobin formation.Conclusions: tamarillo and date palm extract have been proven effective as non-pharmacological interventions in treating anemia in pregnant women. The combination of these two ingredients can be a safe natural alternative and has the potential to increase the success of managing pregnancy anemia